PERSEPSI GURU BIOLOGI MENGHADAPI KURIKULUM 2013 PADA TINGKAT SATUAN SEKOLAH MENENGAH NEGERI DI KOTA PEKANBARU - Suwondo '; Mariani Natalina L; Vivi Triska (Biogenesis, 2014)
The purpose of research is to determine the perception of biology teachers confront the 2013 curriculum at the goverment secondary school in Pekanbaru city. The research conducted in may until june 2013. Determination of the sample is stratified random sampling technique, where the samples used are 25 biology teachers from 10 junior high school and 17 biology teachers from senior high school in pekanbaru. Collecting data using a closed questionnare, and direct interviews. Parameter measured is perception of biology teacher with the indicators used in research are graduates competency standards, content standards, process standards, and standards of evaluation. The result of research at junior high school for graduates competency standards indicator is 2,77, 2,60 for content standards indicator, 3,19 for process standars indicator, and 3,31 for standards of evaluation with average for all indicators are 2,97 belong to category of good. The average result at senior high school for graduates competency standards indicator is 2,87, 3,16 for content standards indicator, 3,10 for process standards indicator, and 3,20 for standards of evaluation with average for all indicators are 3,08 belong to category of good. Based on the result of research concluded that the perception of biology teachers confront the 2013 curriculum at the goverment secondary school in Pekanbaru city is belong to good category.Keywords : 2013 Curriculum, Biology Teachers, Perception, Pekanbaru, SMP, SMA